Selection of variables Affecting Red Blood Cell by Firefly Algorithm - Hamza Obeid, Rehab; J. Sadik, Nazik (Journal of Economics and Administrative Sciences, 2023)
Some maps of the chaotic firefly algorithm were selected to select variables for data on blood diseases and blood vessels obtained from Nasiriyah General Hospital where the data were tested and tracking the distribution of Gamma and it was concluded that a Chebyshevmap method is more efficient than a Sinusoidal map method through mean square error criterion.